HUMAN BREAST MILK FORTIFICATION WITH SKIMMED MILK AND OLIVE OIL FOR WEIGHT GAIN IN VERY LOW BIRTH WEIGHT NEONATES - Waqqas, Arouj; Ahmed, Zeeshan; Farrukh, Huma; Khalid, Hina; Waqar, Talal (Pakistan Armed Forces Medical Journal, 2021)
Objective: To observe the effect of fortification of expressed human breast milk with olive oil and skimmed milk in improving weight gain in very low birth weight neonates and shortening their length of hospital stay.Study Design: A comparative prospective study.Place and Duration of Study: Combined Military Hospital Lahore, from Mar 2018 to Mar 2019.Methodology: Neonates admitted with very low birth weight and gestational age of